Development and validation of HIV-1 Multiplex Serology - Kranz, Lena Mareen; Brenner, Nicole (Journal of immunological methods, 2019)
By inducing immunosuppression in infected patients, human immunodeficiency virus-1 (HIV-1) generates a favorable environment for opportunistic infections and the development of several human cancers. In order to detect individual serum or plasma HIV-1 antibody status for epidemiological studies, high-throughput HIV-1 Multiplex Serology was developed. Seven HIV-1 antigens were recombinantly expressed in E. coli as N-terminal glutathione-S-transferase (GST) fusion proteins that are bound to glutathione-coupled sets of beads with distinct fluorescent color. Combining all bead sets in a suspension array allowed for simultaneous detection of antibodies targeting structural, regulatory and accessory proteins expressed during HIV-1 infection. HIV-1 Multiplex Serology was validated with 244 reference sera whose HIV-1 serostatus had been pre-determined by screening microparticle immunoassay and confirmatory line immunoassay. The multifunctional protein GAG emerged as an excellent marker to determine HIV-1 serostatus with a specificity of 99% (95% CI 96%-100%) and sensitivity of 100% (95% CI 88%-100%). Seropositivity for multiple HIV-1 antigens appeared to be characteristic for HIV-1 infected individuals (median number of antigens recognized in reference assay positive sera: 4; median number of antigens recognized in reference assay negative sera: 0), indicating a broad immune response targeting also regulatory and accessory proteins which may be useful for the identification of antibody patterns specific for infection-associated disease stages. HIV-1 Multiplex Serology performs similarly to conventional HIV-1 serology but eliminates the need for a two-step screening approach with subsequent confirmation assay. Thus, this highthroughput method will facilitate large-scale epidemiological studies of the role of HIV-1 in cancer development.